GENEALOGI INTELEKTUAL PENDIRI MADRASAH DI SUMATERA - Nasution, Neysa Vania (UIN Sumatera Utara, 2021)
Abstract: This paper describes the mindset, contribution and network of madrasah founding actors in Sumtera. The study uses historical science approach as a point of view by collecting related historical sources. Therefore, historically, this study is not limited by time. Some of the scholars who are the focus of the study include. Shaykh Abdullah Ahmad, born in 1878 in Padang Panjang and died in Jati Village, Padang, Shaykh Thaib Umar, Zainuddin Labai El Yunusy, Shaykh Abdul Karim Amrullah, Shaykh Abbas,angkayo Rahmah El Yunusia and several other figures. The pattern of network formation is a network of intellectuals who study in various regions such as Minang Kabau, Padang Panjang, Riau, Palembang, Langkat and Aceh. The long journey of madrasah is inseparable from the long history of the world. Its existence is full of twists and turns in maintaining the existence of Islam, which is something unique to it. Since Indonesia's independence, even long before that, madrasas have contributed a lot to the intellectual life of Muslim communities, especially in Sumatra. Although on the way always get stumbling regulations. The dynamics experienced make Madrasahs always open to discussion. Keywords: Actors, Madrasah, Sumatra